2023
DOI: 10.3389/fped.2023.1086867
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Virus-induced hemophagocytic lymphohistiocytosis in a patient with APECED

Abstract: Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), also known as autoimmune polyglandular syndrome type 1 (APS-1) is a rare autosomal recessive inborn error of immunity (IEI), which is accompanied by immune dysregulation. Hypoparathyroidism, adrenocortical failure and candidiasis are its typical manifestations. Here we report about recurrent COVID-19 in a 3-year-old boy with APECED, who developed retinopathy with macular atrophy and autoimmune hepatitis after the first episode of SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…In a previous study, 12 patients from 11 unrelated families have been identified with homozygous or compound heterozygous variants in AIRE and observed with autoimmune retinopathy ( 10 , 35 – 40 ). In total, 11 of the 12 patients initially had systemic symptoms, including autoimmune hepatitis, mucocutaneous candidiasis, hypoparathyroidism, or adrenal insufficiency, followed by vision loss or nyctalopia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, 12 patients from 11 unrelated families have been identified with homozygous or compound heterozygous variants in AIRE and observed with autoimmune retinopathy ( 10 , 35 – 40 ). In total, 11 of the 12 patients initially had systemic symptoms, including autoimmune hepatitis, mucocutaneous candidiasis, hypoparathyroidism, or adrenal insufficiency, followed by vision loss or nyctalopia.…”
Section: Resultsmentioning
confidence: 99%
“…The initial symptoms of APS1 are usually infection in childhood, followed by hypoparathyroidism by age 10 and adrenal insufficiency by age 15 ( 51 53 ). Keratoconjunctivitis has been long-established as associated with APS1 when the eye is involved ( 54 ), while a limited number of patients with APS1 have been found to present with autoimmune retinopathy ( 10 , 35 – 40 ). A total of 12 reported patients in the literature exhibited with consistent retinal changes resembling retinitis pigmentosa, which showed a pale optic disc, attenuated retinal arterioles, and bone-spicule pigment changes in the periphery with retinal atrophic changes ( 36 ).…”
Section: Discussionmentioning
confidence: 99%